2014
DOI: 10.1159/000362577
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Therapy of Gastric Cancer: A Decisive Step Forward

Abstract: Background: Although its incidence has been steadily decreasing in Western countries, gastric cancer remains a leading cause of cancer deaths worldwide. The detection rate of early-stage cancers is improving; nevertheless, the majority of cases is still diagnosed at later stages with a poor prognosis. Furthermore, the results that can be achieved with surgery have reached a plateau of effectiveness. Summary: Neoadjuvant chemotherapy was successfully introduced first in patients with non-curatively resectable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…While NAC has become a standard of care for patients with gastric and esophagogastric cancer, some studies support omission of NAC, and it is unclear which specific stages, including T2N0, derive OS benefit . In a recent analysis of the MAGIC trial, Smyth et al concluded that the presence of lymph node metastases and not cPR to chemotherapy was the only independent predictor of OS after chemotherapy plus resection, further raising question as to whether NAC provides OS benefit based on T stage .…”
Section: Discussionmentioning
confidence: 99%
“…While NAC has become a standard of care for patients with gastric and esophagogastric cancer, some studies support omission of NAC, and it is unclear which specific stages, including T2N0, derive OS benefit . In a recent analysis of the MAGIC trial, Smyth et al concluded that the presence of lymph node metastases and not cPR to chemotherapy was the only independent predictor of OS after chemotherapy plus resection, further raising question as to whether NAC provides OS benefit based on T stage .…”
Section: Discussionmentioning
confidence: 99%
“…The current study presents the findings of NDLS based chemotherapy in patients with gastric and GEJ cancer in neoadjuvant and metastatic settings. Neoadjuvant treatment remains the gold standard for the treatment of locally advanced gastric cancer, which aims at 'downstaging' the tumor and eliminating the spread of tumor cells or lymph node metastases (36). The available evidence suggests a role for neoadjuvant docetaxel-based chemotherapy in downstaging the cancer, achieving complete surgical resection and probably improving the outcome in patients with locally advanced GAC (37).…”
Section: Discussionmentioning
confidence: 99%